2014
DOI: 10.1007/s11764-014-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivorship training: a pilot study examining the educational gap in primary care medicine residency programs

Abstract: Inadequate training in cancer survivorship represents a barrier to providing adequate cancer follow-up. Inexperience or unawareness of essential survivorship issues could lead to mistakes which affect survivors' health and timely assessment of long-term cancer-associated morbidity. As PCPs will play a key role in the delivery of survivorship care, effective educational opportunities and achievement of competencies in adult cancer survivorship care by primary care trainees are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
4
15
0
Order By: Relevance
“…Unfortunately, efforts have focused on oncologists and a few preventive medicine residency programs with specific curricula for a cancer prevention and control track [26]. Our results support the previous report concerning the need for curricular changes to expand the scope of cultural competency and health disparity education to cancer-related decision-making topics such as prevention, screening, and survivorship [27][28][29]. Primary care physicians in training must acquire an in-depth understanding of the main issues related to cancer care disparities.…”
Section: Discussionsupporting
confidence: 83%
“…Unfortunately, efforts have focused on oncologists and a few preventive medicine residency programs with specific curricula for a cancer prevention and control track [26]. Our results support the previous report concerning the need for curricular changes to expand the scope of cultural competency and health disparity education to cancer-related decision-making topics such as prevention, screening, and survivorship [27][28][29]. Primary care physicians in training must acquire an in-depth understanding of the main issues related to cancer care disparities.…”
Section: Discussionsupporting
confidence: 83%
“…Findings from a study in the United States appear to reflect a similar trend regarding FM and internal medicine residency education in oncology, where 81% of residents expected to care for cancer survivors in their future practice, but only 27% of the residents reported formal education in adult cancer survivorship care [6]. This resulted in only 13% feeling comfortable in their role as a primary care provider for adult cancer survivors.…”
Section: Discussionmentioning
confidence: 86%
“…In the United States, a survey of 77 FM and internal medicine residents from several schools found that only 5% of the participating residents rated themselves as very knowledgeable in long-term follow-up care of adult cancer survivors [ 6 ]. Current postgraduate training education opportunities to enhance knowledge in cancer prevention and control are limited [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address these workforce issues, psychosocial providers need to be integrated into oncology settings, and more education about the needs of cancer survivors will be needed for mental health providers, oncologists, PCPs, and nurses. Innovative educational programmes for physicians, nurses, and psychosocial providers have been developed as part of training curricula 6062 and continuing professional education 63,64 to address this requirement, but their quality and accessibility need to be ensured to educate the workforce at large.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%